The regressional analysis in selection of the sugar beet inbred lines - М. О. Корнєєва; М. В. Власюк; І. В. Власюк; Т. Г. Опанасенко (Plant Varieties Studying and Protection)
The use of regression analysis for estimation of inbred lines is a breeding - oriented method, as it indicates scientifically grounded stages of the further breeding studying of these lines and a strategy of their use. Admissible levels of inbred depression of agriculturally valuable characters are limited in lines of the Verkhnyachka and Lgov geneplasms by two - three generations of self - pollinations, which testifies to the necessity "to keep" the characters of sufficient basis. Linearity of changes of values of the characters with the advancing of inbreeding shows the absence of epistasis or the weakness of their effects which makes suitable the use of an additive-dominant model for determining breeding-genetical value of inbred lines with the aim of their purposeful hybridization for obtaining genetically determined heterosis in F1.